2000
DOI: 10.1073/pnas.070548997
|View full text |Cite
|
Sign up to set email alerts
|

Predicting protein function from structure: Unique structural features of proteases

Abstract: We have noted consistent structural similarities among unrelated proteases. In comparison with other proteins of similar size, proteases have smaller than average surface areas, smaller radii of gyration, and higher C ␣ densities. These findings imply that proteases are, as a group, more tightly packed than other proteins. There are also notable differences in secondary structure content between these two groups of proteins: proteases have fewer helices and more loops. We speculate that both high packing densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
1
27
1
Order By: Relevance
“…Indeed, by using Swiss PDB Viewer (Guex and Peitsch, 1997), the calculated loop (random coil) content percentage of the ScGLU-3 template was 48%, which suggests a high degree of fold flexibility. This value is significantly higher than the average loop content (37.6%) of 154 nonprotease proteins reported previously (Stawiski et al, 2000).…”
Section: Structural Modeling Reveals a Putative Ibscontrasting
confidence: 45%
“…Indeed, by using Swiss PDB Viewer (Guex and Peitsch, 1997), the calculated loop (random coil) content percentage of the ScGLU-3 template was 48%, which suggests a high degree of fold flexibility. This value is significantly higher than the average loop content (37.6%) of 154 nonprotease proteins reported previously (Stawiski et al, 2000).…”
Section: Structural Modeling Reveals a Putative Ibscontrasting
confidence: 45%
“…From a study of structural features of the proteases, Stawiski et al found that they exhibit similar characteristics such as smaller than average surface areas and higher C α densities, regardless of whether or not they were evolutionarily related. 13 They also showed different secondary-structure content relative to the non-proteases. By using these features in a machine-learning approach, they were able to define a set of structural classifiers that could predict whether a protein is a protease or a nonprotease with an accuracy of over 86%.…”
Section: Introductionmentioning
confidence: 98%
“…† Another surface-based attribute is the fractal dimension. This is calculated as by Stawiski et al, 29 by calculating the gradient of the log-log plot of probe radius against molecular surface (calculated by MSMS 45 ). Fractal dimension might be thought of as representing the "crinkliness" of the protein's surface.…”
Section: Attributes For Model Buildingmentioning
confidence: 99%
“…Our method falls into this category as it characterises the simple structural properties of each class of enzymes at the top level of the EC scheme. Our initial work was based on the observations made by Stawiski and co-workers, 29 who noted broad structural differences between proteases and non-proteases. These included such properties as high C a density and lower than average surface areas in proteases when compared to non-proteases.…”
Section: Introductionmentioning
confidence: 99%